Dose uniformity evaluations for gamma radiation processing facility using Monte Carlo simulations and its validation - Raksha Rajput; Jyoti Garg; Jain Reji George; Kalpana Khedkar; P. K. Jothish; N. Jayachandran; Pradip Mukherjee (Radiation Protection and Environment)
The gamma radiation processing facilities (GRAPFs) qualify to obtain the license of operation on the basis of the radiological safety of the facility and the accurate radiation dosimetry in the product. The theoretical dose evaluations in the product are carried out using Monte Carlo simulations in this work. This is required for optimizing the source loading configuration with the best combination of averaged dose rate and dose uniformity ratio (DUR) to maximize the efficiency of the facility. Three different GRAPFs are chosen for the study. The theoretical results of DUR are validated against the commissioning dosimetry with a variation of <10% for the facilities chosen. The simulation tool used is an efficient tool for dose mapping studies of radiation processing facilities of different designs.